2008
DOI: 10.1093/eurheartj/ehn268
|View full text |Cite
|
Sign up to set email alerts
|

Absence of auto-antibodies against cardiac troponin I predicts improvement of left ventricular function after acute myocardial infarction

Abstract: We demonstrate for the first time that the prevalence of cTnI-Abs in patients with AMI has an impact on the improvement of the LVEF over a study period of 6-9 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
118
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(121 citation statements)
references
References 24 publications
2
118
1
Order By: Relevance
“…In general, autoantibodies which form macroanalyte complexes are not believed to be disease-causing although cases associated with autoimmune disorders have been described [16,17] and reports suggesting an association between the presence of autoantibodies against cTnI and cardiomyopathy have been published [18][19][20]. Based on current evidence, the main problem caused by a circulating macroanalyte is that it leads to multiple, possibly invasive, investigations in search of a cause.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, autoantibodies which form macroanalyte complexes are not believed to be disease-causing although cases associated with autoimmune disorders have been described [16,17] and reports suggesting an association between the presence of autoantibodies against cTnI and cardiomyopathy have been published [18][19][20]. Based on current evidence, the main problem caused by a circulating macroanalyte is that it leads to multiple, possibly invasive, investigations in search of a cause.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating troponin autoantibodies are not rare, having been identified in 2%-20% of individuals, with or without cardiac disease, in various studies [20][21][22][23][24]. They may be directed towards cTnI [19,22] or cardiac troponin T [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work from our laboratory and others has focused on the dysregulation of the immune system as an essential modulator of disease induction and progression in heart failure (1,2). In this context, release of cardiac troponin I (TnI) from damaged cardiomyocytes into the circulation is believed to trigger an autoimmune response to TnI (3,4).…”
mentioning
confidence: 99%
“…Most studies assessed anti-troponin I antibodies (9,12,14,(39)(40)(41)(42)(45)(46)(47)(48)50,51,(53)(54)(55)(56)(57)(58), whereas anti-troponin T antibodies were assessed in only 16% (n=1,636) of individuals (11,43,44,49,52) (including 993 individuals where both types of autoantibodies were evaluated) (11,44,49).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, conflicting data have been published concerning the impact on prognosis in heart disease (4). Leuschner et al showed that the absence of autoantibodies against cardiac troponin I predicted an improvement of left ventricular function after an acute myocardial infarction (MI) (11). Doesch et al, however, described a beneficial effect of anti-troponin I autoantibodies in the setting of DCM (improved survival), but not in patients with ICM (12).…”
mentioning
confidence: 99%